2016
DOI: 10.12659/ajcr.898534
|View full text |Cite
|
Sign up to set email alerts
|

Rare Presentation of Gastroesophageal Carcinoma with Rectal Metastasis: A Case Report

Abstract: Patient: Female, 60Final Diagnosis: Gastroesophageal carcinoma with rectal metastasisSymptoms: Bloating • constipation • weight lossMedication: —Clinical Procedure: Endoscopy • flexible sigmoidoscopy • lower endoscopic ultrasoundSpecialty: Gastroenterology and HepatologyObjective:Unusual clinical courseBackground:Gastroesophageal cancers, previously considered rare, are rapidly increasing worldwide. We present here a unique case of gastroesophageal carcinoma with metastasis to the rectum.Case Report:A 60-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…To investigate the characteristics of colon metastasis from gastric cancer, we summarized the reported cases of gastric cancer colon metastasis. Synchronous colorectal metastases differ from metachronous; we found 24 metachronous (1-4,6,14-29) (Table I) and 13 synchronous cases (5,25,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as classified and listed in Table II. Several reports have set the boundary between synchronous and metachronous metastases as diagnosed after 2 months, 6 months, and 1 year from the primary diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…To investigate the characteristics of colon metastasis from gastric cancer, we summarized the reported cases of gastric cancer colon metastasis. Synchronous colorectal metastases differ from metachronous; we found 24 metachronous (1-4,6,14-29) (Table I) and 13 synchronous cases (5,25,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as classified and listed in Table II. Several reports have set the boundary between synchronous and metachronous metastases as diagnosed after 2 months, 6 months, and 1 year from the primary diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…The English literature (PubMed) search for rare sites of esophageal cancer metastasis from 1982 to February 2017 by Osama Shaheen, excluded common sites of metastasis, i.e., the liver, lung, bone, adrenal gland, and brain, and retrieved 147 papers; 25 rare metastatic sites were identified, of which only 10 cases were reported to involve metastasis to the rectum (5). Jasbir Makker et al reported a case of gastroesophageal junction adenocarcinoma with rectal metastasis in 2016 (6), and Ryohei Ono et al reported a case of small bowel metastasis from lower thoracic esophageal cancer in 2018 (7). The overall prognosis of the patients in the above cases was extremely poor.…”
Section: Discussionmentioning
confidence: 99%
“…The most common areas of esophageal cancer metastasis are to the liver and peritoneum [68], regional lymph nodes, lung, pleura, stomach, kidney, adrenals, and bone [8]. The urinary bladder is an extremely rare site of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…There are 5 main routes of metastasis of esophageal and gastric cancer: (1) direct invasion; (2) lymphatic spread; and (3) hematogenous, (4) transperitoneal, and (5) intraluminal implantation [ 6 ]. The most common areas of esophageal cancer metastasis are to the liver and peritoneum [ 6 8 ], regional lymph nodes, lung, pleura, stomach, kidney, adrenals, and bone [ 8 ]. The urinary bladder is an extremely rare site of metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation